2017
DOI: 10.1902/jop.2017.160805
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser‐Microtextured Surface Collar on Marginal Bone Loss and Peri‐Implant Soft Tissue Response: A Systematic Review and Meta‐Analysis

Abstract: Meta-analysis showed that an LMS collar can reduce the amount of MBL and PD compared with a machined-surface collar. Due to high heterogeneity between the included studies, results should be interpreted cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 49 publications
4
18
1
Order By: Relevance
“…While the mean for group B at 6 and 9 months was 1.72 and 1.78 respectively which showed no statistically significant difference between both groups. This was in agreement with Chen et al study in 2017 (26) which was a systematic review and meta-analysis which demonstrated that Peri-implant probing depth around Laser treated implants was shallower than a roughed and machined surface implants.…”
Section: Discussionsupporting
confidence: 91%
“…While the mean for group B at 6 and 9 months was 1.72 and 1.78 respectively which showed no statistically significant difference between both groups. This was in agreement with Chen et al study in 2017 (26) which was a systematic review and meta-analysis which demonstrated that Peri-implant probing depth around Laser treated implants was shallower than a roughed and machined surface implants.…”
Section: Discussionsupporting
confidence: 91%
“…We used the random effects model, which might reduce the effect of heterogeneity . However, these results need to be further validated with more high‐quality and larger‐scale RCTs in the future …”
Section: Discussionmentioning
confidence: 99%
“…Our method also could have made heterogeneity of outcomes increase . However, several previous studies similarly enrolled the RCTs and non‐RCTs to increase the sample size and maximize the measured outcomes . To evaluate and solve this problem, we performed the subgroups analysis according to the study type (RCT or non‐RCT) .…”
Section: Discussionmentioning
confidence: 99%
“…106 Recent systematic reviews and meta-analyses of these designs found that rough or laser microtextured collars had significantly less marginal bone loss if placed subcrestally compared with machined collars. 107,108 Similarly, the platform switching concept was favored as more peri-implant marginal bone was preserved, [109][110][111][112][113][114] but thickness of soft tissues might still influence the amount of crestal remodeling. 115 However, these results must be interpreted with caution, as the studies were very heterogeneous in design and the actual differences in the marginal bone levels between the designs (eg, weighted mean difference of 0.43-0.77 mm) were clinically irrelevant.…”
Section: Implant Collar/platform Designsmentioning
confidence: 99%